Gaza conflict on public perspectives - Fariha Diyana Awang Ali,; Nurul Adawiyah Mohamad Johdi,; Nur 'Izzah Mohammad Shuhaimi,; Jayemogen Shanmugam, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research addresses “The Gaza Conflict on Public Perspectives” to investigate the extent of public awareness and knowledge regarding the conflict. Employing a qualitative study, in which, a questionnaire was adopted from the Arab World for Research and Development (AWRAD) study, the study aims to gather 385 public opinions of Subang Jaya residents to explore attitudes, perspectives and impacts that shape the broader public understanding of the Gaza conflict. The findings analysed through descriptive analysis show that Gaza conflict has a profound and multifaceted impact on public perceptions and behaviors, emphasizing the importance of understanding demographic nuances and adopting nuanced approaches to address the conflict’s root causes and promote peace and stability in the region. This analysis endeavors to offer comprehensive, community-specific insights into the ways the Gaza conflict shapes perceptions within the Subang Jaya community. The research findings are expected to shed light on existing gaps in public knowledge and awareness concerning the Gaza conflict, thereby informing policymakers, educators, and the broader community.